Qualitative Analysis of Social Factors Contributing to Gender Inequality: Evidence from Rural Bangladesh - Ashad, Anjuman; Uddin, Helal; Ety, Jannatul Ferdous (International Journal of Qualitative Research, 2024)
Gender is a sensitive issue in the traditional societal setup of Bangladesh. People hesitate to discuss gender even in the 21st century. The problem of gender inequality has been widespread in Bangladesh since the ancient and medieval periods. Moreover, this problem is more acute in rural parts of the country, where people have less privilege and live in a more conservative society. This qualitative study explored rural communities' social, cultural, and economic structure to determine the social factors of gender inequality in rural Bangladesh. To do that, this study used a qualitative research approach. Employing semi-structured in-depth interviews and critically analyzing secondary data, the research scrutinized the perspectives of male and female village residents across diverse roles, such as students, employees, farmers, homemakers, and entrepreneurs. The findings highlighted several social factors causing gender disparity, including the inescapable influence of patriarchal structures, gender stereotypes, preference for male offspring, child marriage, the notion of girls as liabilities, a lack of awareness, socioeconomic barriers, and a lack of explicit policy. With nearly 60.29% of the total population residing in remote areas where gender gaps persist, this research sheds light on the urgent need for intervention. Moreover, this study provided significant recommendations after critically examining the findings. Finally, the study underlined the imperative for governmental and decision-making bodies to prioritize these findings, advocating for the introduction of comprehensive gender awareness initiatives within rural communities to combat deep-rooted inequalities and pave the way toward a more equitable society.